2020
DOI: 10.1186/s13063-019-4004-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of two Ayurvedic dosage forms for allergic rhinitis: Study protocol for an open-label randomized controlled trial

Abstract: Background: Allergic rhinitis (AR) is an immune response of the nasal mucosa to airborne allergens and involves nasal congestion, watery nasal discharge, itching of the nose, and sneezing. The symptoms of allergic rhinitis may significantly affect a patient's quality of life and can be associated with conditions such as fatigue, headache, cognitive impairment, and sleep disturbances. Various complementary and alternative medicine treatments have been used for this condition in clinical practice. The Ayurveda s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is currently acknowledged that the severe symptoms of AR greatly influence the QOL of patients and are related to various conditions including cognitive impairment, headache, fatigue, and sleep disturbances. 39 Furthermore, the presence of nasal and ocular symptoms among AR individuals contributes to poor QOL, lowered work productivity, and elevated resource utilization. 40 Given the significant changes in QOL among patients with AR, we further assessed the potential relationship between BCL6 of AR are attributed to IgE-regulated responses to various inhaled allergens and Th2 cell-triggered mucosal inflammation.…”
Section: Bcl6 Low Expression Affected Qol Of Patients With Armentioning
confidence: 99%
“…It is currently acknowledged that the severe symptoms of AR greatly influence the QOL of patients and are related to various conditions including cognitive impairment, headache, fatigue, and sleep disturbances. 39 Furthermore, the presence of nasal and ocular symptoms among AR individuals contributes to poor QOL, lowered work productivity, and elevated resource utilization. 40 Given the significant changes in QOL among patients with AR, we further assessed the potential relationship between BCL6 of AR are attributed to IgE-regulated responses to various inhaled allergens and Th2 cell-triggered mucosal inflammation.…”
Section: Bcl6 Low Expression Affected Qol Of Patients With Armentioning
confidence: 99%
“…Allergic rhinitis (AR) is an inflammatory disease of the upper respiratory tract characterized by nasal congestion, watery nasal discharge, itchy nose, and sneezing. It is caused by IgE-mediated reactions against inhaled allergens [ 1 , 2 ] . Epidemiological studies have reported that nearly 10–40% of the global population is affected by AR, with increasing incidence [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, in addition to the standard classical Ayurveda and indigenous medical dosage forms, novel dosage forms such as tablets, capsules, syrups, etc., are emerging to increase palatability (Zaigham et al, 2019). Ready-to-use freeze-dried powder (reconstituted powder) is also a recently explored novel dosage form tested for its safety and efficacy (Dahanayake et al, 2020).…”
Section: Introductionmentioning
confidence: 99%